Effects of aquatic exercise on physical function and fitness among people with spinal cord injury: A systematic review. Issue 11 (March 2017) - Li, Chunxiao; Khoo, Selina; Adnan, Athirah
Abstract: Objective: The aim of this review is to synthesize the evidence on the effects of aquatic exercise interventions on physical function and fitness among people with spinal cord injury. Data source: Six major databases were searched from inception till June 2015: MEDLINE, CINAHL, EMBASE, PsychInfo, SPORTDiscus, and Cochrane Center Register of Controlled Trials. Study appraisal and synthesis methods: Two reviewers independently rated methodological quality using the modified Downs and Black Scale and extracted and synthesized key findings (i.e., participant characteristics, study design, physical function and fitness outcomes, and adverse events). Results: Eight of 276 studies met the inclusion criteria, of which none showed high research quality. Four studies assessed physical function outcomes and 4 studies evaluated aerobic fitness as outcome measures. Significant improvements on these 2 outcomes were generally found. Other physical or fitness outcomes including body composition, muscular strength, and balance were rarely reported. Conclusions and implications of key findings: There is weak evidence supporting aquatic exercise training to improve physical function and aerobic fitness among adults with spinal cord injury. Suggestions for future research include reporting details of exercise interventions, evaluating other physical or fitness outcomes, and improving methodological quality. Abstract : Supplemental Digital Content is available in the text